TEAMWORK AS A MAIN FACTOR OF THE DEVELOPMENT OF GLOBAL SKILLS WHILE FORMING FOREIGN LANGUAGE COMPETENCY IN FUTURE PROFESSIONALS IN THE HOTEL AND RESTAURANT BUSINESS, TOURISM INDUSTRY AND INTERNATIONAL RELATIONS - Svitlana I. Medynska (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2020)
The article covers the issues associated with the implementation of the competency approach while training future professionals in the hotel and restaurant business, tourism industry and international relations for professional interaction, namely the role of teamwork for the development of global skills while forming foreign language competency. Domestic and foreign studies on the set of global skills required for increasing the competitiveness of personality, business and the country as a whole have been analyzed to focus on the most crucial ones including critical thinking, collaboration, communication, creativity, leadership, self-management and social responsibility. The essence of interactive learning and teamwork as a basis for its implementation in the educational process has been considered. The foreign experience on differentiation of concepts “group work” and “team work” has been generalized to substantiate the idea that teamwork is at the core of effective interaction in the class. The basic principles of teamwork in the business environment have been considered to define the ones applicable for developing foreign language competency, and conformity of teamwork to pedagogical conditions which are favourable for the students’ professional interaction has been substantiated. The benefits and downsides of teamwork in learning a foreign language have been analyzed taking into account different stages, types and levels of team development to enable teachers to anticipate and mitigate the drawbacks while enhancing the positive effects of teamwork. In addition, the main models of teamwork and conditions for their effective use have been researched to define the most effective one. It has been concluded that the key to success lies in implementing gradual transformation of the team from the traditional model through the team spirit model to the cutting edge one, considering the academic group studying a foreign language as a team with the teacher performing the role of a team leader, while applying the task force model for the temporary groups created for performing particular tasks, and a virtual model in the current realities of online learning. Such a detailed analysis of teamwork will contribute to its more effective application in the learning process to achieve the synergy effect by creating a real team or a higher quality team depending on the availability of resources, capabilities of the teacher as a team leader at the initial stages, and skills of the team members